Occurrence patterns of crop-foraging sika deer distribution in an agriculture-forest landscape revealed by nitrogen stable isotopes - Hata, Ayaka; Nakashita, Rumiko; Fukasawa, Keita; Minami, Masato; Fukue, Yuko; Higuchi, Naoko; Uno, Hikaru; Nakajima, Yasuhiro; Saeki, Midori; Kozakai, Chinatsu; Takada, Mayura (Dryad, 2021)
Conflicts arising from the consumption of anthropogenic foods by wildlife
are increasing worldwide. Conventional tools for evaluating the spatial
distribution pattern of large terrestrial mammals that consume
anthropogenic foods have various limitations, despite their importance in
management to mitigate conflicts. In this study, we examined the spatial
distribution pattern of crop-foraging sika deer by performing nitrogen
stable isotope analyses of bone collagen. We evaluated whether
crop-foraging deer lived closer to agricultural crop fields during the
winter and spring, when crop production decreases. We found that female
deer in proximity to agricultural crop fields during the winter and spring
were more likely to be crop-foraging individuals. Furthermore, the
likelihood of crop consumption by females decreased by half as the
distance to agricultural crop fields increased to 5-10 km. We did not
detect a significant trend in the spatial distribution of crop-foraging
male deer. The findings of spatial distribution patterns of crop-foraging
female deer will be useful for the establishment of management areas, such
as zonation, for efficient removal of them.